Antimicrobial and Antioxidant Properties of a Bacterial Endophyte, Methylobacterium radiotolerans MAMP 4754, Isolated from Combretum erythrophyllum Seeds - Mampolelo M. Photolo; Vuyo Mavumengwana; Lungile Sitole; Matsobane G. Tlou (International Journal of Microbiology)
This study reports on the isolation and identification of Methylobacterium radiotolerans MAMP 4754 from the seeds of the medicinal plant, Combretum erythrophyllum, for the purposes of investigating antimicrobial and antioxidant activities from this endophyte. The strain identity was confirmed by 16S rRNA-based phylogeny and Scanning Electron Microscopy (SEM). Ethyl acetate and chloroform (1 : 1 v/v) extracts from the endophyte were tested for antimicrobial and antioxidant activity on a total of 7 bacterial species (3 Gram-positive and 4 Gram-negative) using the standard Minimum Inhibitory Concentration (MIC) protocol and Quantitative Radical Scavenging activity using the 2, 2-diphenyl-1-picrylhydrazyl (DPPH) assay, respectively. The MICs were recorded at 250 μg/mL for B. subtilis ATCC 19659, B. cereus ATCC 1076, E. coli ATCC1053, and 62.5 μg/mL for K. oxytoca ATCC 13182 and M. smegmatis ATCC 21293, while an IC50 of 5.65 μg/mL was recorded with the DPPH assay. Qualitative phytochemical analysis was positive for alkaloids, flavonoids, and steroids. Gas chromatography/mass spectrometry (GC/MS) analysis revealed the presence of 9-octadecene, 2,4-dinitrophenyl acetate, and 2(5H)-furanone, which have been previously reported for the targeted activities. M. radiotolerans MAMP 4754 tested positive for antimicrobial and antioxidant activity and this is linked to the production of plant-derived secondary metabolites by this strain.